Single stage management of chronic posterolateral knee dislocation in a middle-aged man - A Case Report. - Qamar, Adnan; Ali, Haider; Muhammad Abdul Shakoor; Amjad, Usman; Shah, Syed Wasif Ali (International Journal of Endorsing Health Science Research, 2021)
Background: Posterolateral knee dislocation rarely occur and might not reduce due to buttonholing of the Femoral condyle into the anteromedial knee joint capsule. These are complex injuries without any clear guidelines in terms of management. Case presentation: 40-year-old male presented with posterolateral knee dislocation due to a road traffic accident. Patient was having posterior cruciate ligament (PCL) injury along with posterolateral corner instability supported by clinical examination and confirmed with radiologic investigations. Management and Results: Patient was managed with single-stage arthroscopic reconstruction of PCL followed by open posterolateral corner ligaments reconstruction. Postoperatively patient had positive functional outcomes with satisfactory international knee documentation committee subjective knee form (IKDC) scores. Conclusion: Posterolateral Corner Injury (PLC) injury with associated PCL injury showed positive results when managed in a single-stage procedure.